PENGARUH EKSPOR, IMPOR, TENAGA KERJA, DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Anindita Ajeng Nur Annisa, (2022)
Economic growth signifies economic development by showing a transformation of economic activity each year that results into an increase in national income which is at the same time very strong in relation to the welfare of the population. Economic growth in Indonesia is affected by several factors, such as exports, imports, labor and investment. This research is used to determine the effect of exports, imports, labor and investment on economic growth in Indonesia. The data used in this study is Indonesia from 1990 - 2020, so the analysis model used is a multiple linear regression model. This study shows the results that exports have no effect on economic growth in Indonesia, while imports, labor and investment have an effect on economic growth in Indonesia.